Qualidade em serviço na saúde auditiva infantil: agendamento, espera e permanência - Ralo, Edlene Jovita Silva (2010)
Introduction: Management of health services has been thoroughly discussed in the literature related to quality standards and client satisfaction. However, very few publications discuss the issue in the Field of Speech Language Pathology and Audiology. Recent publication of Hearing Health Policy in Brazil have raised the need for measurements of quality of the services, aiming at planning, organization and coordination of activities resulting in better services. Goal: The goal of the present study is to describe and discuss processes related to quality services, in particular, time spent in the waiting room, duration of services, an process of scheduling appointments in a Hearing Health Service of High Complexity, specialized in children from birth to three years of age. Method: Three typical periods of diagnostic and hearing aid selection and adaptation of the Centro de Audição na Criança/Derdic were selected. Data collection lasted for nine months, and was obtained through: Schedules for each Day, Patient-flow chart, Children s files and floor plan of the Center. Results: Medical consultation and Visual Response Audiometry - VRA were the most frequently performed procedures, 871 of the 2617 procedures performed. 37% of the families arrive at the service at least two hours ahead of scheduled. The mean length of consult was 2 hours and 13 minutes. There was an increase of one hour when ABR was performed. Professionals were not reliable in adding information related to time of departure (only 47% of the total). Conclusion: The results allowed for a thorough understanding of the processes involved in the daily routine of exams for diagnostic process and hearing aid selection and adaptation in a High complexity service of Hearing Health. The complexity of a service with multiple procedures is difficult to register, but the information provided can bring significant improvement in the quality of the processes. The need for greater involvement of speech pathologists and audiologists in quality management is emphasized, regarding its implications for the implementation of the Hearing Health System